ANALISIS PERBEDAAN KANDUNGAN LIPIDA MIKROALGA (Tetraselmis chuii dan Nannochloropsis oculata) PADA AIR LAUT DAN AIR PAYAU - Maswati Baharuddin (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2011)
This research quality eksperiment with different extracted of lipid microalgae Tetraselmis chuii dan Nannochloropsis oculata from two places from sea water and brachis water with pH and salinity to be different. Culture to do for eigh day just process extracted to do for ± three day. Extraction of lipid that had been done using chloroform : methanol (2:1) . product research can to be different growth and pregnancy womb content of lipid that can to do with use sea water media and brachis water media. The result of the research have found that % total lipid will obtained more when growing by using brackish water medias that is obtained counted 15,9 % for the Tetraselmis of chuii and 17,51% for the Nannochloropsis of oculata, while if using sea-water media only obtained 14,8 % and 16,3%. This matter is influenced by some factors like temperature, light intensity, and salinitas of pH.